Pengaruh Stock Split Terhadap Abnormal Return Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015 - Hersanti Bunga Wurianti; Fauji Sanusi (FEB Universitas Sultan Ageng Tirtayasa, 2017)
This study aims to test whether there are significant Abnormal Return differences in the period before and after Stock Split. The data used in this research is obtained from Indonesia Stock Exchange. Data is processed using SPSS Statistict version 20. The population used in this study is a company that performs stock split in Indonesia Stock Exchange period 2015. The sample of this study amounted to 14 company of total population of 16 companies. Sampling using purposive sampling method. This research uses event study method. This study used Paired Sample T-Test with observation period for 15 days before stock split, the event date and 15 days after stock split. Hypothesis test results show that: There is no significant difference in abnormal return before and after stock split.